The exchange rate, diversification, and distribution in a modified Ricardian model with a continuum of goods - Arslan Ramzi (University of Massachusetts, Department of Economics, 2010)
Several recent empirical and theoretical studies have revived interest in the relationship between the level of the exchange rate and economic development. This paper develops a dynamic model based on the Ricardian framework with a continuum of goods to consider the issue from a somewhat different perspective. In the short run, a devaluation can boost profits in spite of real wage rigidity. Moreover, the resulting diversification can offset the negative consequences for the trade balance of higher employment and profitability at Home. Over the longer run, and in the presence of learning-by-accumulation, the initial boost to profits and investment induced by a devaluation could enable a country to gain a permanent foothold in new sectors at a higher real wage. While directly suppressing the real wage could also lead to diversification, what makes nominal devaluations a particularly useful tool is that these make it possible to expand domestic profits while limiting internal distributional conflict and the ensuing negative effects on development.
Keywords: 330